Los Laboulbeniales, un grupo enigmático de hongos parásitos de insectos - Santamaría, Sergi (Lazaroa, 2001)
The Laboulbeniales are the largest and most diverse group of insect-parastic fungi, with nearly 2000 species and 140 genera. They are ectoparasitic and their vegetative body, called a thallus, remains outside the host, which they only penetrate through an inconspicuous haustorium. Potential Laboulbeniales hosts must meet several requirements, the most important of which are that their imagoes (adults) must overwinter and inhabit wet environments and their populations must be large and stable. According to data from the Iberian Peninsula, the most suitable environments to catch insects with Laboulbeniales are riparian habitats (38,5% of known Iberian Laboulbeniales), aquatic (14,6%) and cavernicolous (10%). Worldwide, Laboulbeniales are currently only known to parasitize 10 orders of insects, out of an approximate total of 33. Eighty percent of Laboulbeniales parasitize beetles (Coleoptera) and 10% live on flies (Diptera). Within the Iberian geographical range, carabids (28,4%) and staphylinids (25,3%) are the coleopteran families with the largest number of Laboulbeniales species. It has been broadly accepted and demonstrated that the Laboulbeniales are highly specialised fungi. The two basic types of specialisation are high specificity for an insect host taxon and preference for growth in very restricted areas of the host body. It seems evident that the Laboulbeniales form a monophyletic group. Their origins and phylogenetic affinities are enigmatic. Recent studies of sequencing of nucleic acids demonstrate their affinity with mycelial Ascomycota of the genus Pyxidiophora.